Novel heat exchanger for cold air intake on spark ignition engine performance - Shwan, Pshtiwan Mohammad Sharif (2021)
The engine intake charge air (EICA) system enhancement technology plays an essential part in vehicle engine performance developments and pollution reduction. The increase in ambient temperature due to global warming and climate change introduced a significant influence on vehicle performance. Same while, EICA temperature increasing affects the engine complete combustion due to the oxygen density per volume reduction in air. Thus, EICA cooling technology becomes one of the best solutions for temperature reduction through intercooler units. This research introduces the influence of direct combustion volumetric effect using a new designed evaporative intercooler heat exchanger (EIHE), direct intercooler device used for engine intake charge air cooling (EICAC) in non-turbocharged vehicles spark-Ignition engines (SI-engines), contributing a new technique method in heat-exchanger designing. Most of the previous studies of conventional intercoolers heat-exchangers (IHE) devices demonstrated a significant influence of EICAC on engine performance. However, it presented low efficient or non-operational in vehicle slow driving speed or stand-still operation. Furthermore, the designs showed non-flexibility in size and low cooling capacity. Therefore, there is a need for a better IHE design with flexibility in size designing suitable for most vehicles, able to function in all environments and weather conditions, with the ability of vehicle performance enhanced. The new design should be functional in both vehicle low-speed driving or stand-still parking operation. Refrigerant medium system technology becomes significant in heat transfer property which helps to design subcooling heat-exchanger. The new EIHE device utilizing the refrigerant medium which presented a better performance than the water cooled IHE reaching lower cooling range temperature and functional in all vehicle condition. The Computational Fluid Dynamics (CFD) simulation was used using ANSYS FLUENT to simulate various EIHE models performance with different air flow rate and temperatures. The EIHE geometry shell-and-tube was designed from steel metal, based on criteria of space available inside the vehicle engine bay. The simulation results presented a significant improvement in cooling performance with temperature reduction lower than the inlet temperatures, offering a very low-pressure drop coefficient. The EIHE design was experimentally validated. For the experimental part, the EIHE device was tested both in the laboratory and real-world. The EIHE operation and performance evaluation investigated in real-world tests. The tests result generally presented a significant cooling performance capability by the developed EIHE almost efficient of 49% - 50% reduction in temperature. The applied vehicle test results presented a significant enhanced improvement in the max power wheel and max torque increasement, and test results of real-world test utilizing the EIHE presented a significant emission reduction of 12.86% of CO, 29.32% CO2, and 29.41% HC. In conclusion, the new designed EIHE successfully meet the required objectives.